Are non-radiation-based imaging modalities effective for objectively assessing and monitoring patients with pectus deformities?. (23rd September 2020) - Hussain, Azhar; Patel, Akshay; Hunt, Ian
Abstract : A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was 'What is the role of non-radiation-based imaging modalities in the management of pectus deformities?'. Altogether 29 papers were found using the reported search, of which 8 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. We conclude that non-radiation-based imaging modalities provide a safe and easily implemented alternative to traditional computed tomography scan assessment for pectus deformities. This is particularly true for deformities on the more severe end of the spectrum and as an aid in providing an on-going assessment tool particularly in treatment modalities requiring a high degree of compliance (external bracing or vacuum bell therapy). Abstract : A best evidence topic was constructed according to a structured protocol.